The nature of blue compact dwarf galaxies - Izotov, Y. (Кинематика и физика небесных тел, 2005)
The studies of blue compact dwarf (BCD) galaxies at the Main Astronomical Observatory of the National Academy of Sciences of Ukraine are reviewed. The following problems are discussed: 1) the importance of BCDs for cosmological studies; 2) properties of extremely metaldeficient BCDs; 3) a primordial helium abundance and the baryon mass fraction in the Universe; 4) heavy element abundances in large samples of BCDs; 5) properties of massive stellar populations; 6) properties of the oldest stellar populations; 7) the evolutionary status of BCDs.